Psychological and Managerial Problems of Modern Higher Education - Knyazeva, Natalya Ð.; Gryaznukhin, Aleksandr G.; Kislyakov, Pavel A.; Esaulov, Vladimir I.; Kekteeva, Yulia I.; Polivara, Zinaida V. (International Review of Management and Marketing, 2016)
The article deals with the psychological and managerial problems of modern higher education, socio-economic features of the system of higher education in Russia, the hierarchy of the objectives of educational psychology, methods of improvement. The paper analyzes the problems of psycho-pedagogical process of high school the principal of which is the formation of the model (profile) specialist, regardless of a particular profession, as well as a flow model of the core competencies of information technology graduate economic direction of Institute. Technological model allows to visualize the whole process of acquiring the students the necessary information, knowledge, skills and experience and thus achieve the level set by the State educational standards, forms the key information and technological competence of the future expert - economist, a graduate of Institute reflects the structure, orientation and sequence of the training activities. The article presents the eleven blocks of technology model with a detailed description. The authors concluded that the psychological, pedagogical and managerial tasks are complex; they can be solved by means of modern psychology, pedagogy and teaching methods. This synthesis must be carried out within the framework of an educational institution all the means of education. Keywords: education, managerial problems, teacher, psychology JEL Classifications: A20; H70; I20